Heterojunction photocatalyst, method for preparing same, and use thereof
Patent Information
- Application Number
- CN202611191730.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]Nb3Cl8具有较窄的带隙可以吸收可见光,但单一Nb3Cl8存在光生电子-空穴复合率高、光催化活性较差等问题,导致其实际光催化应用受限,通过异质结构建等方式可显著改善其光催化性能
[0016]本发明提供了异质结光催化剂及其制备方法和应用。本发明分别用固相烧结法合成八氯化三铌和沉淀法合成二硫化锆,并通过静电吸附构建异质结,从而得到了本发明所述的异质结光催化剂。相比于纯八氯化三铌样品,二硫化锆的负载改变半导体的能带结构,并改善光生载流子的动力学过程,加速光催化反应中的物质传递,从而提升光催化产氢的效率,显著提升光催化产氢的性能。实验表明,催化反应1 h,H2的产率达到3.64 mmol g-1h-1;连续4次光催化产氢循环后,保持显著的催化效率。该光催化材料具有优异的催化活性和良好的稳定性,具有较好的应用前景。
Smart Images

Figure CN122999231A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photocatalytic materials technology, specifically to heterojunction photocatalysts, their preparation methods, and applications. Background Technology
[0002] Since the Industrial Revolution, global energy demand has continued to grow, and the widespread use of fossil fuels has led to a continuous increase in the concentration of greenhouse gases in the atmosphere. Climate change and its related environmental and economic impacts have become increasingly significant. Solar energy is widely considered a clean, abundant, and inexhaustible renewable energy source. Therefore, directly converting sunlight into chemical energy to achieve green hydrogen production has become one of the key pathways to achieve both energy and environmental goals. Photocatalytic water splitting has shown great potential in this field: by generating and separating photogenerated loads, water molecules are catalytically decomposed to produce hydrogen under relatively mild reaction conditions, possessing the potential for "zero carbon emissions." However, despite significant progress in material design and reaction mechanisms over the past few years, existing photocatalytic systems still face several bottlenecks in practical applications: the limited spectral coverage of a single photocatalyst restricts the generation and utilization of photogenerated carriers; rapid recombination of photogenerated electron-hole pairs in the bulk or interfacial regions reduces catalytic efficiency; and high dependence on noble metal catalytic materials raises issues of cost and resource sustainability. Therefore, it is urgent to achieve a coordinated improvement in spectral response, load separation, and surface catalytic activity through material design and interface engineering.
[0003] Nb3Cl8 has a narrow band gap that allows it to absorb visible light, but single Nb3Cl8 exhibits problems such as high photogenerated electron-hole recombination rates and poor photocatalytic activity, limiting its practical photocatalytic applications. Its photocatalytic performance can be significantly improved through heterostructure construction. However, there are currently no reports on Nb3Cl8 and its heterojunctions as photocatalytic hydrogen production. Summary of the Invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a heterojunction photocatalyst, its preparation method and application. The heterojunction photocatalyst provided by the present invention is constructed by loading zirconium disulfide (ZrS2) nanoparticles on the surface of niobium octachloride (Nb3Cl8) to form a heterojunction, which has high photoinduced charge separation and transfer ability, thereby having high efficiency in photocatalytic hydrogen production.
[0005] This invention provides a heterojunction photocatalyst comprising niobium octachloride and zirconium disulfide nanoparticles electrostatically adsorbed on the surface of the niobium octachloride. Preferably, the molar ratio of niobium octachloride to the zirconium disulfide nanoparticles is 1:(0.5~1). More preferably, the molar ratio of niobium octachloride to the zirconium disulfide nanoparticles is 1:0.75.
[0006] In the heterojunction photocatalyst provided by this invention, a heterojunction structure exists between the surface of niobium octachloride and the zirconium disulfide nanoparticles. Specifically, the zirconium disulfide is anchored to the surface of niobium octachloride via electrostatic adsorption to form a heterojunction structure.
[0007] The present invention also provides a method for preparing a heterojunction photocatalyst, comprising the following steps: stirring niobium octachloride and zirconium disulfide nanoparticles in an aqueous ethanol solution, ultrasonically dispersing, centrifuging, and freeze-drying to obtain a heterojunction photocatalyst.
[0008] Specifically, this invention involves adding an ethanol-water dispersion of niobium octachloride to an ethanol-water dispersion of zirconium disulfide nanoparticles, stirring, ultrasonically dispersing, centrifuging, and freeze-drying to obtain a heterojunction photocatalyst. More specifically, niobium octachloride is ultrasonically dispersed in an ethanol-water solution to obtain an ethanol-water dispersion of niobium octachloride; zirconium disulfide nanoparticles are ultrasonically dispersed in an ethanol-water solution to obtain an ethanol-water dispersion of zirconium disulfide nanoparticles; then, the ethanol-water dispersion of niobium octachloride is added to the ethanol-water dispersion of zirconium disulfide nanoparticles, stirred, ultrasonically dispersed, centrifuged, and freeze-dried to obtain a heterojunction photocatalyst. In some embodiments of this invention, the stirring time is 1 h to 2 h, and the ultrasonic dispersion time is 1 h to 2 h.
[0009] Preferably, the ratio of niobium octachloride, zirconium disulfide nanoparticles, ethanol, and water is (0.09~0.11) mmol : (0.05~0.1) mmol : (20~70) mL : (20~70) mL. More preferably, the ratio of niobium octachloride, zirconium disulfide nanoparticles, ethanol, and water is (0.09~0.11) mmol : 0.075 mmol : (20~70) mL : (20~70) mL. Even more preferably, the ratio of niobium octachloride, zirconium disulfide nanoparticles, ethanol, and water is 0.1 mmol : 0.075 mmol : 35 mL : 35 mL.
[0010] The niobium octachloride of this invention is synthesized from niobium pentachloride and niobium powder via solid-state sintering, specifically by heat-treating a mixture of niobium pentachloride and niobium powder under vacuum conditions. In some embodiments of this invention, the niobium octachloride is prepared by the following method: under vacuum conditions, niobium pentachloride and niobium powder are heat-treated at 800℃~840℃ for 70 h~75 h to obtain niobium octachloride; the molar ratio of niobium pentachloride and niobium powder is (7.9~8.1):(6.9~7.1); wherein the heating rate of the heat treatment is 4.5℃ / min~5.5℃ / min.
[0011] The zirconium disulfide nanoparticles of this invention are synthesized by a precipitation method, specifically by adjusting the pH of a mixed aqueous solution of zirconium oxychloride and sodium sulfide, followed by heating, stirring, and sonication. More specifically, the zirconium disulfide nanoparticles are prepared by the following method: heating and stirring a mixed aqueous solution of zirconium oxychloride and sodium sulfide at pH 8-10 at 45°C-65°C for 25-45 min, followed by sonication for 30-120 min to obtain zirconium disulfide nanoparticles. In some embodiments of this invention, zirconium oxychloride is dissolved in water to obtain a zirconium oxychloride aqueous solution, sodium sulfide aqueous solution is added to the zirconium oxychloride aqueous solution, the pH of the solution is adjusted to 8-10, heating and stirring are continued for 25-45 min, followed by sonication for 30-120 min, washing and drying the precipitate to obtain zirconium disulfide nanoparticles. Preferably, the ratio of zirconium oxychloride, sodium sulfide nonahydrate, and water is (0.2-0.4) g : (0.4-0.6) g : (20-40) mL. Preferably, the heating and stirring time is 25 min to 35 min.
[0012] The present invention also provides a method for photocatalytic water production of hydrogen, comprising the following steps: applying light energy to an aqueous solution containing sodium sulfide and sodium sulfite in the presence of any of the aforementioned heterojunction photocatalysts or heterojunction photocatalysts obtained by any of the aforementioned preparation methods.
[0013] Preferably, in the aqueous solution containing sodium sulfide and sodium sulfite, the concentration ratio of sodium sulfide to sodium sulfite is (0.3~0.4) mol / L : (0.2~0.3) mol / L. Preferably, the dosage of the heterojunction photocatalyst is 0.75 g / L~0.85 g / L.
[0014] This invention does not impose special restrictions on the operation and conditions for the photocatalytic water-to-hydrogen production; conventional operations familiar to those skilled in the art can be followed. In some embodiments of this invention, in a reactor, any of the aforementioned heterojunction photocatalysts or the heterojunction photocatalysts prepared by any of the aforementioned methods are added to an aqueous solution containing sodium sulfide and sodium sulfite, stirred and mixed, then ultrasonically mixed to obtain a suspension. Argon gas is then introduced to replace the gas in the reactor containing the suspension, and light energy is applied to the suspension. Preferably, argon gas is introduced to replace the gas in the reactor containing the suspension, and the argon gas introduction time is preferably 10 min to 20 min.
[0015] In this invention, light energy is provided by illumination from a light source. The type of light source is not particularly limited; any conventional light source known to those skilled in the art for photocatalytic hydrogen production from water is acceptable. Preferably, a Xe lamp (i.e., a xenon lamp, whose emission spectrum approximates sunlight) is used as the simulated light source. In some embodiments of this invention, a 300W Xe lamp is used as the light source, equipped with a 420 nm cutoff filter. Under the illumination of the light source, the photocatalytic system undergoes a photocatalytic hydrogen production reaction from water.
[0016] This invention provides a heterojunction photocatalyst, its preparation method, and its applications. The invention synthesizes niobium octachloride via solid-state sintering and zirconium disulfide via precipitation, respectively, and constructs a heterojunction through electrostatic adsorption, thereby obtaining the heterojunction photocatalyst described in this invention. Compared to pure niobium octachloride, the loading of zirconium disulfide alters the band structure of the semiconductor and improves the kinetics of photogenerated carriers, accelerating mass transfer in the photocatalytic reaction, thus improving the efficiency of photocatalytic hydrogen production and significantly enhancing its performance. Experiments show that after 1 h of catalytic reaction, the yield of H2 reaches 3.64 mmol g. -1 h -1 After four consecutive photocatalytic hydrogen production cycles, the material maintains significant catalytic efficiency. This photocatalytic material exhibits excellent catalytic activity and good stability, showing promising application prospects. Attached Figure Description
[0017] Figure 1 The image shows the SEM image of the second Nb3Cl8@ZrS2 sample obtained in Example 2.
[0018] Figure 2 The EDS image is of sample No. 2 of Nb3Cl8@ZrS2 obtained in Example 2;
[0019] Figure 3 The X-ray diffraction patterns are those of the Nb3Cl8@ZrS2 sample obtained in Example 2, the pure Nb3Cl8 obtained in Comparative Example 3, and the pure ZrS2 obtained in Comparative Example 4.
[0020] Figure 4 Zeta potential test diagrams of pure Nb3Cl8 obtained in Comparative Example 3 and pure ZrS2 obtained in Comparative Example 4.
[0021] Figure 5 The UV-Vis diffuse reflectance spectrum of Nb3Cl8@ZrS2 sample No. 2 obtained in Example 2;
[0022] Figure 6 The photocurrent response test diagrams are of the Nb3Cl8@ZrS2 sample No. 2 obtained in Example 2, the pure Nb3Cl8 obtained in Comparative Example 3, and the pure ZrS2 obtained in Comparative Example 4.
[0023] Figure 7Schematic diagram of photocatalytic hydrogen production from water using a mixed solution of Na2S and Na2SO3;
[0024] Figure 8 This is a comparison chart of the photocatalytic hydrogen production efficiency of the products of Examples 1-3 and Comparative Examples 1-5 of the present invention;
[0025] Figure 9 The image shows the cyclic stability of the photocatalytic hydrogen production performance of the Nb3Cl8@ZrS2 sample obtained in Example 2. Detailed Implementation
[0026] This invention discloses a heterojunction photocatalyst, its preparation method, and its applications. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired results. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments, and those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.
[0027] The present invention will be further described below with reference to the embodiments:
[0028] Example 1
[0029] The preparation method of Nb3Cl8@ZrS2 heterojunction photocatalyst is as follows:
[0030] 1. Preparation of Nb3Cl8
[0031] Niobium pentachloride and niobium powder were thoroughly mixed at a molar ratio of 8:7 and placed in a quartz tube. The tube was then evacuated and sealed. The mixture was then transferred to a muffle furnace with the following parameters: heating rate of 5 °C / min, heating to 817 °C, and holding at that temperature for 72 h. The mixture was then allowed to cool naturally. The resulting solid was then ground into powder in an agate mortar to obtain Nb3Cl8.
[0032] 2. Preparation of ZrS2
[0033] Dissolve 0.3 g of zirconium oxychloride and 0.5 g of sodium sulfide nonahydrate in 30 mL of deionized water. Heat the zirconium oxychloride solution at 55 °C with stirring and add sodium sulfide solution dropwise. Adjust the pH of the solution to 9 and continue heating and stirring for 30 min. Then, sonicate for 120 min to obtain a white suspension. Centrifuge the white suspension, wash it with 60 mL of deionized water, and centrifuge three times at 12000 r / min for 5 min. Then wash it with 60 mL of ethanol and centrifuge three times at 12000 r / min for 3 min to obtain a white centrifuged solid. Place the obtained white centrifuged solid in an oven to dry at 60 °C for 12 h. After natural cooling, grind the dried white solid into powder in an agate mortar to obtain ZrS2.
[0034] 3. Preparation of Nb3Cl8@ZrS2 heterojunction
[0035] Niobium octachloride and zirconium disulfide were ultrasonically dispersed in an ethanol-water solution consisting of 35 mL of ethanol and 35 mL of deionized water, respectively. The ratio of niobium octachloride:zirconium disulfide:ethanol:deionized water was 0.1 mmol:0.05 mmol:35 mL:35 mL. After ultrasonic dispersion for 1.5 h, niobium octachloride dispersion and zirconium disulfide dispersion were obtained. The niobium octachloride dispersion was vigorously stirred at 1000 rpm and zirconium disulfide dispersion was slowly added dropwise. Stirring was continued for 1.5 h. Then, the mixture was ultrasonicated for 1.5 h. After centrifugation, the precipitate was frozen with liquid nitrogen and transferred to a freeze dryer. The parameters were set to -60 °C and incubated for 72 h to obtain the first Nb3Cl8@ZrS2 heterojunction sample.
[0036] Example 2
[0037] Compared with Example 1, the only difference is that the ratio of niobium octachloride:zirconium disulfide:ethanol:deionized water is 0.1 mmol:0.075 mmol:35 mL:35 mL, which yields the second Nb3Cl8@ZrS2 heterojunction sample.
[0038] Example 3
[0039] Compared with Example 1, the only difference is that the ratio of niobium octachloride:zirconium disulfide:ethanol:deionized water is 0.1 mmol:0.1 mmol:35 mL:35 mL, which yields Nb3Cl8@ZrS2 heterojunction sample No. 3.
[0040] Comparative Example 1
[0041] Compared with Example 1, the only difference is that the ratio of niobium octachloride:zirconium disulfide:ethanol:deionized water is 0.1 mmol:0.025 mmol:35 mL:35 mL, which yields Nb3Cl8@ZrS2 heterojunction catalyst sample No. 5.
[0042] Comparative Example 2
[0043] The Nb3Cl8@ZrS2 heterojunction catalyst sample No. 6 was obtained by mixing niobium octachloride, zirconium disulfide, ethanol, and deionized water in a ratio of 0.1 mmol:0.2 mmol:35 mL:35 mL.
[0044] Comparative Example 3
[0045] Niobium pentachloride and niobium powder were thoroughly mixed at a molar ratio of 8:7 and placed in a quartz tube. The tube was then evacuated and sealed. The mixture was then placed in a muffle furnace with the following parameters: heating rate of 5 °C / min, heating to 817 °C, and holding at that temperature for 72 h. The mixture was then allowed to cool naturally. The resulting solid was then ground into powder in an agate mortar to obtain pure Nb3Cl8.
[0046] Comparative Example 4
[0047] 0.3 g of zirconium oxychloride and 0.5 g of sodium sulfide nonahydrate were dissolved in 30 mL of deionized water. The zirconium oxychloride solution was heated and stirred at 55 °C while sodium sulfide solution was added dropwise. The pH of the solution was adjusted to 9, and the heating and stirring continued for 30 min. Then, the solution was sonicated for 120 min to obtain a white suspension. The white suspension was centrifuged, washed with 60 mL of deionized water, and centrifuged three times at 12000 r / min for 5 min. Then, it was washed with 60 mL of ethanol and centrifuged three times at 12000 r / min for 3 min to obtain a white centrifuged solid. The obtained white centrifuged solid was dried in an oven at 60 °C for 12 h. After natural cooling, the dried white solid was ground into powder in an agate mortar to obtain pure ZrS2.
[0048] Comparative Example 5
[0049] The preparation method of mechanically mixed Nb3Cl8 / ZrS2 is as follows:
[0050] Take 0.1 mmol of niobium octachloride and 0.075 mmol of zirconium disulfide and place them in an agate mortar. Grind and mix them thoroughly for 5 min to obtain mechanically mixed Nb3Cl8 / ZrS2.
[0051] The purity of niobium pentachloride, niobium powder, zirconium oxychloride and sodium sulfide nonahydrate described in this invention is above analytical grade, which can ensure the purity of the product. Otherwise, the purity of the product will be affected, thereby affecting the catalytic performance of the obtained catalyst.
[0052] Product characterization
[0053] (1) SEM and EDS characterization
[0054] The second Nb3Cl8@ZrS2 sample obtained in Example 2 was observed using a scanning electron microscope (SEM) equipped with energy dispersive spectroscopy (EDS). The results are shown in [link to SEM]. Figure 1 and Figure 2 . Figure 1 The image shows the SEM image of the second Nb3Cl8@ZrS2 sample obtained in Example 2. It can be seen that the surface of Nb3Cl8 is loaded with several ZrS2 nanoparticles, and the size of the second Nb3Cl8@ZrS2 sample is about 3 μm. Figure 2 The EDS image of the Nb3Cl8@ZrS2 sample obtained in Example 2 shows that Nb, Cl, Zr and S elements are uniformly distributed in the heterojunction.
[0055] (2) X-ray diffraction test
[0056] X-ray diffraction (XRD) tests were performed on the Nb3Cl8@ZrS2 sample obtained in Example 2, the pure Nb3Cl8 obtained in Comparative Example 3, and the pure ZrS2 obtained in Comparative Example 4. The results are as follows: Figure 3 As shown, Figure 3 The X-ray diffraction patterns are shown for Nb3Cl8@ZrS2 sample No. 2 obtained in Example 2, pure Nb3Cl8 obtained in Comparative Example 3, and pure ZrS2 obtained in Comparative Example 4. It can be seen that the prepared ZrS2 sample has poor crystallinity; the X-ray diffraction pattern of the prepared Nb3Cl8 sample matches the international standard card library PDF No. 04-007-1838; the peak positions of the X-ray diffraction pattern of the prepared Nb3Cl8@ZrS2 sample No. 2 are basically consistent with those of the Nb3Cl8 sample, possibly because the ZrS2 loading is low and the crystallinity is poor, causing its peaks to be masked.
[0057] (3) Zeta potential test
[0058] Zeta potentials were measured on the pure Nb3Cl8 obtained in Comparative Example 3 and the pure ZrS2 obtained in Comparative Example 4, and the results are as follows: Figure 4 As shown, Figure 4 The figures show the Zeta potentials of pure Nb3Cl8 obtained in Comparative Example 3 and pure ZrS2 obtained in Comparative Example 4. It can be seen that the Nb3Cl8 and ZrS2 prepared in this invention are negatively and positively charged, respectively, in an ethanol-water solution, and can be used to assemble heterojunctions via electrostatic adsorption.
[0059] (4) Ultraviolet-visible diffuse reflectance test
[0060] The UV-Vis diffuse reflectance test was performed on the Nb3Cl8@ZrS2 sample obtained in Example 2, and the results are as follows: Figure 5 As shown, Figure 5 The image shows the UV-Vis diffuse reflectance spectrum of the Nb3Cl8@ZrS2 sample No. 2 obtained in Example 2. It can be seen that the Nb3Cl8@ZrS2 heterojunction prepared in this invention exhibits strong absorption across the entire spectrum, greatly improving the generation and utilization efficiency of photogenerated carriers, indicating that the catalyst has high catalytic activity under sunlight.
[0061] (5) Transient-steady-state photocurrent testing
[0062] The photocurrent response of the Nb3Cl8@ZrS2 sample obtained in Example 2, the pure Nb3Cl8 obtained in Comparative Example 3, and the pure ZrS2 obtained in Comparative Example 4 was measured. The measurement method was as follows: a standard three-electrode system was used, in which an electrode made of catalyst slurry (composed of catalyst powder, Nafion solution, and ethanol dispersant) coated on FTO conductive glass was used as the working electrode, an Ag / AgCl electrode (filled with saturated KCl solution) was used as the reference electrode, and a platinum sheet was used as the counter electrode. The test was carried out in a 0.5 mol / L Na2SO4 aqueous electrolyte to ensure a stable ionic conductivity environment. During the test, at the open circuit potential, a xenon lamp was used to simulate visible light irradiation, and the voltage signal across the sampling resistor was collected using a CHI 760E electrochemical workstation by periodically switching the light source, thereby recording the transient photocurrent response curve (it curve) of the working electrode under alternating light and dark conditions to evaluate the photogenerated carrier separation and transport efficiency of the material.
[0063] The measurement results are as follows Figure 6 As shown, Figure 6 The photocurrent response test graphs are for the Nb3Cl8@ZrS2 sample No. 2 obtained in Example 2, the pure Nb3Cl8 obtained in Comparative Example 3, and the pure ZrS2 obtained in Comparative Example 4. Figure 6 As can be seen, the photocurrent of the Nb3Cl8@ZrS2 sample 2 is significantly enhanced compared to Nb3Cl8 and ZrS2, confirming that the heterojunction interface effectively promotes charge separation and exhibits excellent photoelectrochemical performance. This result demonstrates that the construction of heterojunctions can significantly improve the photogenerated charge separation efficiency, thereby endowing the material with excellent photocatalytic hydrogen production activity.
[0064] (6) Photocatalytic hydrogen production performance test
[0065] Under ultrasonic conditions, 5 mg of the photocatalysts from Examples 1-3 and Comparative Examples 1-5 were dispersed in 6 mL of a mixed solution containing 0.35 M Na₂S and 0.25 M Na₂SO₃. The mixture was rapidly stirred (600 rpm) and then ultrasonicated for 3 min at 150 W. The reactor was then sealed, and Ar was continuously introduced into the system for 15 min to replace the gas inside. Subsequently, a 300 W Xe lamp equipped with a 420 nm cutoff filter was used as the light source to irradiate the reaction system, and the mixture was rapidly stirred (600 rpm) to perform photocatalytic hydrogen production from water. Finally, the hydrogen yield was analyzed using an Agilent 8860GC gas chromatograph. Figure 7 As shown, Figure 7 A schematic diagram simulating photocatalytic hydrogen production from water using a mixed solution of Na2S and Na2SO3.
[0066] The photocatalytic hydrogen production efficiency of the products from Examples 1-3 and Comparative Examples 1-5 was analyzed, and the results are as follows: Figure 8 , Figure 8 This is a comparison chart of the photocatalytic hydrogen production efficiency of the products from Examples 1-3 and Comparative Examples 1-5 of the present invention. Figure 8 It can be seen that the Nb3Cl8@ZrS2 catalyst sample 2 exhibits the highest hydrogen production efficiency, with a yield reaching 3.64 mmol g. -1 h -1 The photocatalytic hydrogen production performance of Nb3Cl8@ZrS2 is much higher than that of pure Nb3Cl8 and pure ZrS2. As the loading of ZrS2 increases, the hydrogen production efficiency of Nb3Cl8@ZrS2 shows a trend of first increasing and then decreasing. When the molar ratio of ZrS2:Nb3Cl8 is higher than 0.075:0.1, the hydrogen production efficiency decreases significantly. Moreover, the mechanically mixed Nb3Cl8 / ZrS2 obtained in Comparative Example 5 does not significantly improve the hydrogen production efficiency compared with pure Nb3Cl8, which proves that the Nb3Cl8@ZrS2 heterojunction catalyst constructed by electrostatic adsorption in this invention can significantly improve the photocatalytic hydrogen production efficiency of water.
[0067] The photocatalytic hydrogen production cycle stability of the Nb3Cl8@ZrS2 sample obtained in Example 2 was analyzed, and the results are as follows: Figure 9 , Figure 9 This is a cyclic stability diagram of the photocatalytic hydrogen production performance of the Nb3Cl8@ZrS2 sample 2 obtained in Example 2. Figure 9 It can be seen that after four consecutive photocatalytic hydrogen production cycles, the catalytic efficiency basically does not decrease.
[0068] As demonstrated by the above embodiments, this invention synthesizes niobium octachloride using a solid-state sintering method and zirconium disulfide using a precipitation method. A heterojunction is then constructed via electrostatic adsorption to obtain the Nb3Cl8@ZrS2 heterojunction photocatalyst. Compared to the pure niobium octachloride sample, the zirconium disulfide loading alters the semiconductor's band structure and improves the dynamics of photogenerated carriers, accelerating mass transfer in the photocatalytic reaction and thus enhancing the efficiency of photocatalytic hydrogen production. The H2 yield reaches 3.64 mmol g after 1 hour of catalytic reaction. -1 h -1 After four consecutive photocatalytic hydrogen production cycles, the material maintains significant catalytic efficiency. This photocatalytic material exhibits excellent catalytic activity and good stability, showing promising application prospects.
[0069] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A heterojunction photocatalyst, characterized in that, It includes niobium octachloride and zirconium disulfide nanoparticles electrostatically adsorbed on the surface of the niobium octachloride.
2. The heterojunction photocatalyst according to claim 1, characterized in that, The surface of the niobium octachloride has a heterojunction structure with the zirconium disulfide nanoparticles.
3. The heterojunction photocatalyst according to claim 1, characterized in that, The molar ratio of niobium octachloride to zirconium disulfide nanoparticles is 1:(0.5~1).
4. The heterojunction photocatalyst according to claim 1, characterized in that, The molar ratio of niobium octachloride to zirconium disulfide nanoparticles is 1:0.
75.
5. A method for preparing a heterojunction photocatalyst, characterized in that, Includes the following steps: Niobium octachloride and zirconium disulfide nanoparticles were stirred in an aqueous ethanol solution, ultrasonically dispersed, centrifuged, and freeze-dried to obtain a heterojunction photocatalyst.
6. The preparation method according to claim 5, characterized in that, The feed-to-liquid ratio of niobium octachloride, zirconium disulfide nanoparticles, ethanol and water is (0.09~0.11) mmol: (0.05~0.1) mmol: (20~70) mL: (20~70) mL.
7. The preparation method according to claim 5, characterized in that, The feed-to-liquid ratio of niobium octachloride, zirconium disulfide nanoparticles, ethanol and water is (0.09~0.11) mmol: 0.075 mmol: (20~70) mL: (20~70) mL.
8. The preparation method according to claim 5, characterized in that, The ultrasonic dispersion time is 1 h to 2 h.
9. The preparation method according to claim 5, characterized in that, The niobium octachloride was prepared by the following method: under vacuum conditions, niobium pentachloride and niobium powder were heat-treated at 800℃~840℃ for 70 h~75 h to obtain niobium octachloride; the molar ratio of niobium pentachloride and niobium powder was (7.9~8.1):(6.9~7.1); The zirconium disulfide nanoparticles were prepared by the following method: a mixed aqueous solution of zirconium oxychloride and sodium sulfide with a pH of 8-10 was heated and stirred at 45℃-65℃ for 25 min-45 min, and then sonicated for 30 min-120 min to obtain zirconium disulfide nanoparticles; the ratio of zirconium oxychloride, sodium sulfide nonahydrate and water was (0.2-0.4) g:(0.4-0.6) g:(20-40) mL.
10. A method for photocatalytic water production of hydrogen, characterized in that, Includes the following steps: In the presence of the heterojunction photocatalyst according to any one of claims 1 to 4 or the heterojunction photocatalyst obtained by the preparation method according to any one of claims 5 to 9, light energy is applied to an aqueous solution containing sodium sulfide and sodium sulfite.
